(untitled) (Swiss Medical Weekly, 2014)
Intravenous bisphosphonates are widely used to treat osteoporosis and bone metastasis in cancer patients The risk of hypocalcaemia is a rare but underestimated side effect of anti-resorptive treatment. Clinically apparent hypocalcaemia is mostly related to high-dose treatment with zoledronate and denosumab in cancer patients Particular caution is mandatory in all malnourished patients and patients with renal failure who are treated for either bone metastases or osteoporosis. To avoid serious hypocalcaemia, pre-treatment calcium and vitamin D status should be assessed and corrected if appropriate.